Deposit Inflows and Outflows in Failing Banks: The Role of Deposit Insurance - MARTIN, CHRISTOPHER; PURI, MANJU; UFIER, ALEXANDER (Journal of Finance, 2026)
ABSTRACT Using unique, daily, account‐level data, we investigate deposit outflows and inflows in a distressed bank. We observe an outflow of uninsured depositors following bad regulatory news. Both regular and temporary deposit insurance reduce outflows. We provide important new evidence that, simultaneous with deposit outflows, deposit inflows are first order. Uninsured deposit outflows were largely offset with new insured deposit inflows as the bank approached failure, with the bank increasing term deposit rates. This phenomenon holds in a large sample of banks that faced regulatory action, suggesting that insured deposit inflows are an important mechanism that weakens depositor discipline.